Association of dietary patterns with the risk of central obesity in Chinese adults: the China Nutrition and Health Surveillance 2015–2017 - Nan, Jing; Yang, Yuxiang; Li, Fusheng; Cai, Shuya; Piao, Wei; Zhao, Liyun; Xu, Jiao; Yu, Dongmei (Frontiers in Nutrition, 2025)
BackgroundDiet is one of the important factors affecting obesity, especially central obesity. Dietary patterns can reflect the comprehensive effect of food and nutrients more comprehensively and truthfully, and effectively study the relationship between diet and human health. Therefore, it is of great significance to study the association between dietary patterns and central obesity to promote the change of residents' dietary behavior in the direction of healthier.ObjectivesThe purpose of this study was to extract the dietary patterns among Chinese adults aged 18 and above and to explore its relationship with central obesity.MethodThe data was derived from the China Nutrition and Health Surveillance (2015–2017), and the sample participants were obtained by stratified, multi-stage, and random sampling. A total of 61,222 adults aged 18 or older with complete dietary information from mainland China were included in this study. The dietary frequency questionnaire was used to collect food intake information of the respondents, exploratory factor analysis was used to analyze the dietary patterns, and the relationship between dietary patterns and central obesity was analyzed by multivariate logistic regression.ResultsFour dietary patterns were extracted: classical pattern, vegetarian pattern, sugar-oil pattern, and western staple food pattern. The analysis showed that the higher the adherence to the classical pattern, the lower the risk of central obesity. In contrast, higher adherence to the sugar-oil pattern was associated with a higher risk of central obesity.ConclusionThe risk of central obesity was lower in people with classic pattern. The sugar-oil pattern was not conducive to reducing the risk of central obesity in Chinese adults. These findings provide nationally representative evidence for the development of strategies for the prevention and control of central obesity in Chinese adults.